HOSPITAL ADMISSIONS OF ADOLESCENTS IN SERGIPE, FROM 2002 TO 2012 - Nynemberg Menezes Guimarães; Eleonora Ramos de Oliveira; Anna Klara Bohland (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To describe hospital admissions of adolescents living in Sergipe, Northeast Brazil, from 2002 to 2012. Methods: Descriptive study, based on data collected from the Hospital Information System of the Unified Health System. Hospital admissions were divided into four groups of causes: by pregnancy, childbirth and puerperium; by external causes; by primary care conditions; and other causes. Numbers, percentages and coefficients were used in the analysis and compared by year, sex, age (from 10 to 14 and from 15 to 19 years), and the average annual cost of hospitalizations for each group of causes. Results: In the period studied, there were 149,850 hospital admissions of adolescents, 58.4% for pregnancy, childbirth and puerperium, 9.3% for primary care conditions, 8.3% for external causes and 24.0% for other causes. All coefficients decreased from 2002 to 2012 by 39.7%. Primary care conditions had the most significant reduction (143.1%), followed by external causes (60.1%). As for age groups, the coefficients for external causes in the age group of 15 to -19 years, and for pregnancy, childbirth and puerperium, in the age range of 10 to 14 years, are noteworthy because they remained stable in the period. There was an increase in the average cost of all admissions (234.7%), especially for external causes. Conclusions: Health actions to reduce hospital admission due to conditions sensitive to primary care should be given more attention, as well as those related to external causes and pregnancy, among adolescents living in Sergipe, Northeastern Brazil.